Kekosongan Norma Penguatan Fungsi Checks and Balances Badan Pemusyawaratan Desa Pasca UU Desa 2024 - Fakhri Awaludin Istiabudi; I Dewa Gede Herman Yudiawan (Jurnal Hukum, Administrasi Publik dan Negara, 2026)
This study examines the normative gap concerning the strengthening of the Village Consultative Body (BPD) as a checks and balances institution following the enactment of Law Number 3 of 2024 on Villages. The research employs a normative legal approach using statutory, conceptual, and literature-based analyses of relevant legal sources. The findings reveal that the 2024 Village Law primarily emphasizes extending the village head's term of office from six to eight years without providing adequate reinforcement of the BPD's authority, supervisory functions, or institutional capacity. As a result, an imbalance of power between the village head and the BPD may emerge, potentially weakening the BPD's oversight role, reducing community representation, and limiting accountability mechanisms at the village level. Furthermore, the weakened institutional position of the BPD increases the risk of excessive concentration of local power and may undermine democratic village governance. Therefore, this study recommends strengthening the legal framework through implementing regulations that enhance the BPD's authority, improving institutional capacity through continuous training and development, and reinforcing horizontal accountability mechanisms to promote transparent, participatory, accountable, and democratic village governance.